Determination of Spatiotemporal Variations in Heavy Metal Concentration through Orontes River - Ece Kılıç; Mehmet Fatih Can (Turkish Journal of Agriculture: Food Science and Technology)
Water quality in surface waters is an important concern since it directly affects public health. Therefore, to provide adequate quality of water, monitoring studies have been conducted all around the world. In this study, multivariate statistical methods were used to understand the spatial and temporal changes in heavy metal concentration (including As, Cd, Cr, Cu, Fe, Hg, Mn, Pb, Zn) through Orontes River. Monitoring study results belonging to 5 different stations in Orontes River was obtained from State of Hydraulic Works and evaluated according to Box and Whisker plots, two-way PERMONAVA analysis and Mann-Kendall trend test. Results indicated that heavy metal concentrations has been increasing year by year. However, there is no significant spatial change in heavy metal concentration and rather homogenous distribution was observed through Orontes River. On the other hand, Iron (Fe) concentration in river was seasonal depended with no significant trend.